Optical properties of reduced graphene oxide-coated tellurite glass doped at different erbium composition - Azlina Yahya,; Muhammad Noorazlan Abd Azis,; Suriani Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Graphene-based nanomaterials have significant potential to be used as coating materials for glass performance. In this work, reduced graphene oxide (rGO)-coated tellurite glass was synthesized via melt-quenching and low-cost spray coating techniques for improving the optical properties in the glassy matrix. The structural properties investigated using X-Ray Diffraction (XRD) confirmed the structural arrangement of an amorphous nature phase meanwhile, Scanning Electron Microscopy (SEM) analysis proved the morphological structure images of rGO onto the tellurite glass surface. The refractive index value of rGO-coated glass was found higher in the range of 2.402 - 2.775 due to the graphene-based effects. The optical bandgap energy value of rGO-coated glass was improved from 1.913 - 2.980 eV which correlated to the changes in rGO absorption characteristics. The Urbach energy showed a high number of defects in absorption with the presence of rGO structures. By virtue of improved optical properties, the rGO-coated glass may be beneficial to be used as a glass coating material f or high optical performance of fiber optics.